Building Agency by Co-creating Knowledge with Farmers: Enabling and Empowering for Demand-driven interventions (BACKFEED) - Fisher, Monica; Marenya, Paswel (International Maize and Wheat Improvement Center, 2023)
New approaches of listening to farmer communities are needed to support impactful, demand-driven agricultural interventions. This study describes the process of cocreating with farmers and stakeholders in Malawi and Zambia—a hybrid farmer feedback system that listens to farmers first and is socially inclusive. An initial design solution links the knowledge/content library of the GeoFarmer application with Viamo’s interactive voice response (IVR), supplemented by participatory processes, in-person information exchanges, and community and household sensitization. Our objective is a feedback system where farmers across a spectrum of social groups regularly, spontaneously, and sustainably obtain information, provide and receive feedback, and network with their peers. Critical to designing an inclusive farmer feedback system is understanding and addressing social exclusion in agricultural information channels, including digital channels, and heightened exclusion faced by people with more than one social or economic vulnerability. Our design solution focuses on technology that even many resource-poor farmers have at their fingertips right now—basic phones (not smartphones). Viamo’s IVR in local languages enables reaching and hearing from farmers with access to basic phones and encouraging participation of those who might otherwise be excluded due to limited literacy (ICT, reading and writing ability, national languages). Working with communities, we are devising approaches, using existing community resources, to give access to mobile phones to those in need. Various approaches (e.g., role models, household methodologies) are to be implemented to challenge and help positively transcend social norms that disadvantage some groups in agricultural information channels.